Elevated CO2 concentration induces changes in plant growth, transcriptome, and antioxidant activity in fennel (Foeniculum vulgare Mill.) - Jo, Na-Yeon; Lee, Junkyung; Byeon, Ji-Eun; Park, Hong-Jin; Ryoo, Jong-Won; Hwang, Sun-Goo (Frontiers in Plant Science, 2022)
Introduction Fennel (Foeniculum vulgare Mill.) is widely used to produce natural bio-materials. Elevated CO2 (eCO2) concentrations in the atmosphere improve the net photosynthesis of plants. Methods The aim of the present study was to investigate distinct changes in fennel growth characteristics and phytonutrient contents under different CO2 concentrations. The effects of 400 and 800 ppm concentrations on plant growth and antioxidant activity were observed under hydroponics. Results and Discussion Plant growth was improved by eCO2 concentrations. We also observed diverse changes in nutrient solution (pH, electrical conductivity, and dissolved oxygen) and environmental factors (temperature and humidity) in greenhouse under light or dark conditions. Electrical conductivity increased under dark and eCO2 conditions, whereas the pH decreased. Additionally, we performed transcriptome analysis and identified CO2-responsive differentially expressed genes. In the 800 ppm group, genes involved in photosynthesis and Karrikin response were upregulated whereas those involved in syncytium formation were downregulated. Four upregulated differentially expressed genes involved in flavonoid biosynthesis and total flavonoid content were relatively increased under the 800 ppm CO2 condition. In contrast, antioxidant activity, including total phenolic content, scavenging activity, ferric ion reducing antioxidant power, and reducing power were decreased in fennel under relatively high eCO2 concentrations. Moreover, different light intensities of 12 or 24 lx did not affect the growth and antioxidant activity of fennel, suggesting eCO2 has a stronger effect on plant improvement than light intensity. The results of the present study enhance our understanding of the positive effects of CO2 on the growth and antioxidant activity of fennel.